En Plaque Meningioma Presenting as a Cutaneous Nodule - Apostolakis, Sotirios (Asian J Neurosurg, 2019)
Meningiomas are the most common central nervous system tumor and can be found anywhere in the neuraxis. In rare cases, they may extend beyond the cranial vault, while cases without evidence of intracranial mass existence have also been reported. Here, we report the case of a 64-year-old male patient with a history of craniectomy for parasagittal meningioma, who presented at the emergency department with onset of focal seizures. The patient underwent nonenhanced brain computed tomography scan which was indicative of recurrence of the mass. The patient was scheduled for craniotomy and excision of the mass. He also expressed his desire to have a scalp nodule removed concomitantly. Thickening of the meninges underlying the nodule was observed but without indication of a space-occupying lesion. Both histological examinations were suggestive of Grade II, atypical meningiomas. A case of a subcutaneous meningioma in a patient with a history of surgically excised parasagittal meningioma is presented. Radiologic evidence of dural proliferation underlying the mass was suggestive of an en plaque meningioma secondary to iatrogenic dissemination of tumor cells.